A Magnetic Gated Nanofluidic Based on the Integration of a Superhydrophilic Nanochannels and a Reconfigurable Ferrofluid. Issue 7 (14th December 2018) - Wang, Dianyu; Zheng, Shuang; Liu, He; Tang, Jiayue; Miao, Weining; Wang, Huanting; Tian, Ye; Yang, Hua; Jiang, Lei
Abstract: The design of intelligent gating in nanoscale is the subject of intense research motivated by a broad potential impact on science and technology. However, the existing designs require complex modification and are unstable, which restrict their practical applications. Here, a magnetic gated nanofluidic is reported based on the integration of superhydrophilic membranes and reconfigurable ferrofluid, which realizes the gating of the nanochannel by adjusting the steric configuration of the ferrofluid. This system could achieve ultrahigh gating ratio up to 10 000 and excellent stability up to 130 cycles without attenuation. Experiments and theoretical calculations demonstrate that the switch is controlled by the synergy of magnetic force and the interfacial tension. The introduction of ferrofluid and superhydrophilic nanochannels in this work presents an important paradigm for the nanofluidic systems and opens a new and promising avenue to various developments in the fields of materials science, which may be utilized in medical devices, nanoscale synthesis, and environmental analysis. Abstract : A magnetic‐gated nanofluidic based on the integration of superhydrophilic membranes and a reconfigurable ferrofluid is reported. The fluid realizes the gating of the nanochannel by adjusting the ferrofluid's steric configuration. The system achieves an ultrahigh gating ratio up to 10 000 and excellent stability up to 130 cycles without attenuation.